Effect of Calcium-sensitizing Mutations on Calcium Binding and Exchange with Troponin C in Increasingly Complex Biochemical Systems - Tikunova, Svetlana B. (2010)
The calcium dependent interactions between troponin C (TnC) and other thin and thick filament proteins play a key role in regulation of cardiac muscle contraction. Five hydrophobic residues Phe(20), Val(44), Met(45), Leu(48) and Met(81) in the regulatory domain of TnC were individually substituted with polar Gln, to examine the effect of these mutations that sensitized isolated TnC to calcium on: 1) calcium binding and exchange with TnC in increasingly complex biochemical systems and 2) calcium sensitivity of actomyosin ATPase. The hydrophobic residue mutations drastically affected calcium binding and exchange with TnC in increasingly complex biochemical systems, indicating that side chain intra- and inter-molecular interactions of these residues play a crucial role in determining how TnC responds to calcium. However, the mutations that sensitized isolated TnC to calcium did not necessarily increase the calcium sensitivity of the troponin (Tn) complex or reconstituted thin filaments with or without myosin S1. Furthermore, the calcium sensitivity of reconstituted thin filaments (in the absence of myosin S1) was a better predictor of the calcium dependence of actomyosin ATPase activity than that of TnC or the Tn complex. Thus, both the intrinsic properties of TnC and its interactions with the other contractile proteins play a crucial role in modulating calcium binding to TnC in increasingly complex biochemical systems